2009
DOI: 10.1197/jamia.m2687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-interruptive Medication Laboratory Monitoring Alerts in Ambulatory Care

Abstract: We found that non-interruptive medication laboratory monitoring alerts were not effective in improving receipt of recommended baseline laboratory test monitoring for medications. Further work is necessary to optimize compliance with non-critical recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 29 publications
1
62
0
Order By: Relevance
“…Other approaches could be possible as well. For example, we rigorously avoided the forcing function approach, but that approach has shown benefit in studies of medication safety prompting systems 24,25 even though it also leads to high override rates. 26 As another example, a recent Cochrane review 1 found that computer-generated reminders delivered on paper were effective in changing practice and that providing space for physicians to respond led to greater effect size; including an explanation of the reminder, however, which we avoided, also improved effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches could be possible as well. For example, we rigorously avoided the forcing function approach, but that approach has shown benefit in studies of medication safety prompting systems 24,25 even though it also leads to high override rates. 26 As another example, a recent Cochrane review 1 found that computer-generated reminders delivered on paper were effective in changing practice and that providing space for physicians to respond led to greater effect size; including an explanation of the reminder, however, which we avoided, also improved effect size.…”
Section: Discussionmentioning
confidence: 99%
“…While prior literature either evaluates only physician test ordering 5,6 or overall test completion, 8,9 rarely are both reported. 20,40 Most studies have reported only completion rates, usually determined from claims data, 41 while we have separated outcomes into test ordering and patient completion of ordered tests.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report clinician ordering only, 5,6 while others report overall test completion rates. [7][8][9][10][11] In addition, little information is available about why patients fail to complete ordered laboratory tests.…”
Section: Introductionmentioning
confidence: 99%
“…23,[38][39][40][41][42][43][44][45] One study (4%) was conducted in Europe and Australia. 46,47 Thirteen studies (57%) evaluated CCDSSs in primary care,* 5 (22%) in hospital outpatient ambulatory care, 26,31,33,36,44 and 5 (22%) in hospital inpatient care. 22,25,32,34 Intervention.-Fifteen different CCDSSs were studied, of which 6 (40%) were focused solely on laboratory testing, † 5 (33%) also included other reminders such as treatment options, [27][28][29]31,39,[41][42][43] and 4 (27%) were not stand-alone systems, but were developed by an EHR software vendor.…”
Section: Included Studiesmentioning
confidence: 99%
“…[20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Eight studies (35%) were conducted in Europe. 23,[38][39][40][41][42][43][44][45] One study (4%) was conducted in Europe and Australia.…”
Section: Included Studiesmentioning
confidence: 99%